Measuring power - Coburn, J. W. (Strength and Conditioning Journal, 2012)
Power is arguably the most important performance attribute in sport. Because of this, it is essential that strength and conditioning coaches be familiar with various tests to measure power output in their athletes. This will allow them to assess individual athlete and team strengths and weaknesses and to more effectively prescribe conditioning programs. The purpose of this article was to present an overview of power and to describe tests that can be used by the strength and conditioning professional to assess this important component of performance in their athletes.